Induction chemoradiation in stage IIIA/N2 non-small-cell lung cancer: a phase 3 randomised trial. Issue 9998 (12th September 2015) - Pless, Miklos; Stupp, Roger; Ris, Hans-Beat; Stahel, Rolf A; Weder, Walter; Thierstein, Sandra; Gerard, Marie-Aline; Xyrafas, Alexandros; Früh, Martin; Cathomas, Richard; Zippelius, Alfred; Roth, Arnaud; et al.
Summary: Background: One of the standard options in the treatment of stage IIIA/N2 non-small-cell lung cancer is neoadjuvant chemotherapy and surgery. We did a randomised trial to investigate whether the addition of neoadjuvant radiotherapy improves outcomes. Methods: We enrolled patients in 23 centres in Switzerland, Germany and Serbia. Eligible patients had pathologically proven, stage IIIA/N2 non-small-cell lung cancer and were randomly assigned to treatment groups in a 1:1 ratio. Those in the chemoradiotherapy group received three cycles of neoadjuvant chemotherapy (100 mg/m 2 cisplatin and 85 mg/m 2 docetaxel) followed by radiotherapy with 44 Gy in 22 fractions over 3 weeks, and those in the control group received neoadjuvant chemotherapy alone. All patients were scheduled to undergo surgery. Randomisation was stratified by centre, mediastinal bulk (less than 5 cm vs 5 cm or more), and weight loss (5% or more vs less than 5% in the previous 6 months). The primary endpoint was event-free survival. Analyses were done by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT00030771 . Findings: From 2001 to 2012, 232 patients were enrolled, of whom 117 were allocated to the chemoradiotherapy group and 115 to the chemotherapy group. Median event-free survival was similar in the two groups at 12·8 months (95% CI 9·7–22·9) in the chemoradiotherapy group and 11·6 months (8·4–15·2) in the chemotherapy group (p=0·67). Median overall survival was 37·1 months (95% CI 22·6–50·0) with radiotherapy, compared with 26·2 months (19·9–52·1) in the control group. Chemotherapy-related toxic effects were reported in most patients, but 91% of patients completed three cycles of chemotherapy. Radiotherapy-induced grade 3 dysphagia was seen in seven (7%) patients. Three patients died in the control group within 30 days after surgery. Interpretation: Radiotherapy did not add any benefit to induction chemotherapy followed by surgery. We suggest that one definitive local treatment modality combined with neoadjuvant chemotherapy is adequate to treat resectable stage IIIA/N2 non-small-cell lung cancer. Funding: Swiss State Secretariat for Education, Research and Innovation (SERI), Swiss Cancer League, and Sanofi.